Knowledge, attitude and practice on sexual health among students of Centre for Foundation Studies - Othman, Noratikah; Abdul Aziz, Norsyuhadah; Jamaludin, Sumaiyah @ ThandarSoe (IIUM Press, 2020)
Introduction: Sexual health is not merely just avoiding infectious disease or unwanted pregnancy, but it is broader issue that required serious attention. People with sexually transmitted infection or unwanted pregnancy also have the chances to be sexually healthy. In order to be sexually healthy, ones must recognize the sexual rights that we share, having the access to get the sexual health education, and able to communicate with the healthcare providers regarding the issues of sexual health and empowered to prevent sexually transmitted disease and unwanted pregnancy. Aims: This study aims to determine the level of knowledge, attitudes, and practices on sexual health among the students of centre for foundation studies (CFS). Method: A cross-sectional study was conducted among 320 participants by using a close-ended question. Result: The results showed that, there were high level of knowledge on sexual health among CFS students with excellent understandings on non-permissible premarital sexual intercourse displayed by their non-experience confessions. Conclusion: This study findings can be used for future to develop intervention in order to decrease the sexual health problems by enlightening the students on proper knowledge, attitude and practice on sexual health.